Is divisive politics making Americans sick? Associations of perceived partisan polarization with physical and mental health outcomes among adults in the United States - Nayak, Sameera S.; Fraser, Timothy; Panagopoulos, Costas; Aldrich, Daniel P.; Kim, Daniel (Social science & medicine (1982), 2021)
To investigate whether changes in perceived partisan polarization since the 2016 US presidential election and current perceptions of polarization are associated with the onset of physical and mental health conditions in adults. We surveyed a nationally-representative sample (n = 2752) of US adults between December 2019 and January 2020. We used multivariable logistic regression to estimate associations between perceived polarization and the incidence of hypertension, high cholesterol, obesity, diabetes, and anxiety, depressive, and sleep disorders in or after 2016 and current self-rated health. Our secondary exposure variables measured perceptions of mass and elite polarization at the state and national level. Perceived mass polarization measured perceptions of the partisan gap between Democrat and Republican voters; perceived elite polarization measured perceptions of the partisan gap between Democrat and Republican elected officials. Participants reporting an increase in polarization had 52–57% higher odds of developing depressive disorders (OR = 1.52, 95% CI: 1.01, 2.29, P = 0.047) and anxiety disorders (OR = 1.57, 95% CI: 1.07, 2.29, P = 0.02) compared to participants who perceived no change in polarization. Those reporting high (vs. low) levels of perceived state-level mass polarization had a 49% higher odds of incident depressive disorders (P = 0.03). Participants who perceived high levels of state-level elite polarization reported a 71% higher odds of incident depressive disorders (P = 0.004) and a 49% higher odds of incident sleep disorders (P = 0.03). Perceptions of partisan polarization may represent important factors that are linked to the onset of mental health and sleep disorders. •Perceived partisan polarization has plausible effects on physical and mental health.•Increased perceived polarization was associated with incident anxiety and depression.•No significant associations were found with hypertension or high cholesterol.•Perceived partisan polarization may be a key determinant of mental health outcomes.